2022
DOI: 10.2147/opth.s385040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Behavioral-Based Risk Factors (Eye Cosmetic and Tobacco Use) of Symptomatic Dry Eye Disease in Four Middle Eastern Countries: Lebanon, Syria, Jordan, and Palestine

Abstract: To estimate the prevalence of symptomatic dry eye disease (DED) in four Middle Eastern Countries and investigate the association between behavioral-based risk factors and severity of DED. Patients and Methods: Population-based cross-sectional study of 1463 participants from 4 Mediterranean countries (Lebanon, Syria, Jordan, and Palestine). The Arabic version of the Ocular Surface Disease Index (ARB-OSDI) questionnaire was used to estimate the prevalence and severity of symptomatic DED using an online format su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…26 Prevalences for countries having only a single estimate indicated DED values of 69% for Palestine (West Bank), 52% for Jordan, 27.2% for Iraq, 10% for United Arab Emirates, 28.5% for Tunisia, 36.4% for Lebanon, and 40% for Libya. 26 Additional sources have indicated a DED prevalence of 15% for Israel, 27 65.2% for Syria, 28 and 52.8% for Turkey. 29 Taken together, the varied outcomes reported in the above-mentioned studies indicate that the overall prevalence of DED in MENA is not clearly established.…”
Section: Epidemiology Of Dry Eye Globally and In Menamentioning
confidence: 99%
See 1 more Smart Citation
“…26 Prevalences for countries having only a single estimate indicated DED values of 69% for Palestine (West Bank), 52% for Jordan, 27.2% for Iraq, 10% for United Arab Emirates, 28.5% for Tunisia, 36.4% for Lebanon, and 40% for Libya. 26 Additional sources have indicated a DED prevalence of 15% for Israel, 27 65.2% for Syria, 28 and 52.8% for Turkey. 29 Taken together, the varied outcomes reported in the above-mentioned studies indicate that the overall prevalence of DED in MENA is not clearly established.…”
Section: Epidemiology Of Dry Eye Globally and In Menamentioning
confidence: 99%
“…The OSDI is a useful tool for assessing the severity of DED. Patients are considered positive for DED if their total OSDI score is ≥13, with further subdivisions into Clinical Ophthalmology 2024:18 https://doi.org/10.2147/OPTH.S436027 DovePress 683 mild (score [13][14][15][16][17][18][19][20][21][22], moderate (score [23][24][25][26][27][28][29][30][31][32], and severe (score . The panel also suggested that a visual analogue scale of DED symptoms may provide a quick and reliable assessment of disease severity and patient burden.…”
Section: Diagnostic Procedures In Ded Patient Interviewmentioning
confidence: 99%